2022
DOI: 10.3390/children9111600
|View full text |Cite
|
Sign up to set email alerts
|

Positive Attention Bias Trained during the Rethink Therapeutic Online Game and Related Improvements in Children and Adolescents’ Mental Health

Abstract: Attentional bias towards positive stimuli is considered a resilience factor for mental health and well-being. The aim of the present study was to analyze the effects of an attentional bias training for positive faces in a preventive therapeutic game for children and adolescents. The sample of 54, which consisted of children and adolescents aged between 10–16 years, played the REThink game, which included an attentional bias training level based on the visual search paradigm, where children had the task to quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The game is promising, given the findings of the studies investigating its efficacy and effectiveness [7][8][9][10][11][12] and it follows recommendations from current literature 20 . It is unique, given that there is a limited percentage of preventive games and that the game has a validated gamified assessment system 21 .…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The game is promising, given the findings of the studies investigating its efficacy and effectiveness [7][8][9][10][11][12] and it follows recommendations from current literature 20 . It is unique, given that there is a limited percentage of preventive games and that the game has a validated gamified assessment system 21 .…”
Section: Methodsmentioning
confidence: 95%
“…The present research therefore aimed to test if the REThink therapeutic game is effective as a standalone intervention for improving the mental health and emotion-regulation abilities for children and adolescents that experienced CM. We hypothesized that the participants in the REThink therapeutic game will report similar robust improvements in these outcomes to those documented in the previous trials [7][8][9][10][11][12] , relative to the control condition after the intervention. Based on previous findings on moderators for the treatment efficacy showing that CM is associated with poor treatment outcomes 13 , we expected that improvements in the outcomes for the REThink intervention will be lower for the youths presenting with higher severity of CM, or with additional risk factors such as insecure parent attachment.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies testified to the effectiveness of gamified attentional bias modification mobile apps in reducing emotional symptoms in children and adolescents. The ReThink game was developed based on the ABM-positive-search, which is a gamified ABM designed to train attention toward positive faces (David & Magurean, 2022). A study tested the effect of the ReThink game on attentional biases and mental health in children and adolescents between 10-16 years (David & Magurean, 2022).…”
Section: Gamification Of Mobile Attentional Bias Modificationmentioning
confidence: 99%
“…The ReThink game was developed based on the ABM-positive-search, which is a gamified ABM designed to train attention toward positive faces (David & Magurean, 2022). A study tested the effect of the ReThink game on attentional biases and mental health in children and adolescents between 10-16 years (David & Magurean, 2022). The study showed that the game significantly increased children's attention to positive stimuli (David & Magurean, 2022).…”
Section: Gamification Of Mobile Attentional Bias Modificationmentioning
confidence: 99%